2020
DOI: 10.1080/15384047.2020.1727702
|View full text |Cite
|
Sign up to set email alerts
|

Combined targeting of EGFR and HER2 against prostate cancer stem cells

Abstract: Progression of prostate cancer has been associated with EGFR and HER2 activation and to tumorinitiating cells contribution toward chemotherapy resistance. We investigated the efficacy of a dual intervention against EGFR and HER2 to deplete the tumor-initiating cells, optimize the chemotherapy management and prevent the progression of castration-resistant prostate cancer (CRPC) cells. Using DU145, PC3, and 22Rv1 CRPC cell lines, biochemical analysis revealed activation of EGFR, HER2, MAPK, and STAT3 in DU145 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…We found that ERBB2 (v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2, a.k.a., HER2 ) is expressed in-antiphase in “N” with respect to nodules “A” and “B” but in-phase between these two nodules. This finding justifies the reports that ERBB2 activation is associated with tumor-initiating cells contribution and progression of prostate cancer [ 69 ].…”
Section: Resultssupporting
confidence: 91%
“…We found that ERBB2 (v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2, a.k.a., HER2 ) is expressed in-antiphase in “N” with respect to nodules “A” and “B” but in-phase between these two nodules. This finding justifies the reports that ERBB2 activation is associated with tumor-initiating cells contribution and progression of prostate cancer [ 69 ].…”
Section: Resultssupporting
confidence: 91%
“…Despite the initial response to androgen deprivation therapy (ADT), the majority of patients relapse with a poor prognosis stage of castration-resistant prostate cancer (CRPC). Patients with CRPC cannot be cured currently and the mortality remains high [ 3 , 4 ]. Thus, understanding of the mechanisms underlying PCa progression is essential for molecular diagnosis and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The higher number of significant concurrently mutated genes in other molecular pathways may explain the decreased efficacy of PARP inhibitors in prostate cancer harboring BRCA1 mutations compared to those with BRCA2 mutation. For example, ERBB2 alterations co-segregate strongly with BRCA1 and are known to be associated with tumor aggressiveness in primary prostate cancer, tumor progression and invasion in advanced prostate cancer, and shorter time to castration-resistance ( 8 ). Similarly, alterations in NOTCH1 also co-segregate with BRCA1 .…”
Section: Discussionmentioning
confidence: 99%